Impact of NFATC1 and NFATC4 genotypes on the quality of life self-assessments in 16-18-year-old adolescents with primary hypertension - O.G. Ivanko; A.V. Tovma (Zaslavsky O.Yu., 2018)
Background. Studies aimed at phenotyping of the NFATC gene variations may be promising for further understanding of the pathogenesis and clinical manifestations of arterial hypertension in young people. The aim of the study was to determine the effect of the NFATC1 and NFATC4 gene variability on the quality of life (QoL) assessments according to the Short Form-36 (SF-36) questionnaire in adolescents with primary hypertension. Materials and methods. The object of the study - 84 adolescents aged 16-18 years, students of the medical university. All of them were questioned twice, at the age of 16 and 18 years, using the SF-36 questionnaire. Clinical investigations: the office blood pressure measurements, 24-hour blood pressure monitoring, laboratory and instrumental data aimed to exclude symptomatic hypertension. Also, the frequency of the NFATC1 and NFATC4 genes single nucleotide polymorphisms rs7240256, rs11665469, rs754505, rs2229309 and gene expression were evaluated. Results. The study has shown an increased expression of these genes which was 3 and 17 times higher than the reference levels. The TT genotype rs11665469 of NFATC1 gene was associated with the lowest QoL scores in hypertensive patients, which amounted to only 75 % of the ideal level, due to dissatisfaction of patients with their general health status, vitality and mental health; role functioning conditioned by the physical state, social functioning and bodily pain. Conclusions. The correlation was established between low QoL self-assessments in carriers of the genotype TT rs11665469 NFATC1 in hypertensive adolescents. The data obtained for the first time testifies that in adolescents, the rs11665469 NFATC1 genotypes influence the self-assessments of general condition. So, this phenomenon can be involved in the pathogenesis of hypertension in children.